Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1550147716662787
|View full text |Cite
|
Sign up to set email alerts
|

Meta-survey on medium access control surveys in wireless sensor networks

Abstract: Medium access control layer has been the hotbed of research in the field of wireless sensor networks since huge amount of research in wireless sensor networks has focused on saving energy and lately reducing latency. For the most part, medium access control layer solutions in wireless sensor networks are entrusted to save energy, to reduce latency, and at times to ensure reliability perhaps through cross-layer solutions. In this article, we review the surveys at medium access control layer and point to readers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 162 publications
0
7
0
Order By: Relevance
“…Arain et al [2] reviewed 30 surveys papers regarding on MAC in WSN. This work classified the survey's article based on the subject-wise, which are: general, taxonomy, quality of service, performance, eccentric, and energy-efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Arain et al [2] reviewed 30 surveys papers regarding on MAC in WSN. This work classified the survey's article based on the subject-wise, which are: general, taxonomy, quality of service, performance, eccentric, and energy-efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…Generally, WSN consists of tiny nodes called motes and one or multiple nodes named as a sink or a base station (BS) [2]. As shown in fig.1, the node hardware is composed of a detecting module, a data processing module, a transceiver module, and a power module [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…Kakria et al in [13] only cover single channel protocols. Finally, Arain et al in [14] only cover multichannel contention-free protocols. In Table 2 a summary and a comparison of our study and recent surveys are shown.…”
Section: Introductionmentioning
confidence: 99%
“…1. Due to the small and finite nature of the transceiver nodes when juxtaposed to conventional Wireless Sensor Networks, there exist limitations that are associated with these transceiver nodes as a result of their energy utilization in the network in terms of these given phases: "storing, processing, sensing, and most importantly the delivery of the Vital sign [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%